Amplicon metabarcoding analysis of bio-extract and its potential on plant growth promotion - THANAKORN SAENGSANGA; WASSANA PHANURAK (Society for Indonesian Biodiversity, 2023)
Abstract. Saengsanga T, Phanurak W. 2023. Amplicon metabarcoding analysis of bio-extract and its potential on plant growth promotion. Biodiversitas 24: 916-922. Bio-extract is a mixture of existing organic waste and molasses in the presence of a suitable carbon source by aerobic and/or anaerobic bacteria. In this study, the mineral constitution, bacterial diversity, and effects of the bio-extract on rice growth were investigated. The bio-extract contained various mineral elements, especially nitrogen, potassium, calcium, iron, and magnesium, at concentrations of 248.56, 124.48, 2100.75, 732.68, and 112.60 mg L-1, respectively. The amounts of plant growth regulators, including indole-3-acetic acid (IAA) and total cytokinins, were 0.26 and 1.02 mL L-1, respectively. 16S rRNA-based metagenomic libraries yielded 39,892 amplicon sequence reads corresponding to 32 operational taxonomic units (OTUs). The Shannon index, Chao 1 index, Gini-Simpson index, and Good's coverage value were 2.68, 32.0, 0.74, and 1.0, respectively. Firmicutes (49.4%), Proteobacteria (45.5%) and Actinobacteria (5.1%) were the predominant phyla. A various concentration of bio-extract (0.0, 0.1, 0.5, 1.0, and 1.5% (v/v)) was determined for their effects on the growth of rice seedlings (Oryza sativa L. var. KDML105). The result revealed that highest root and shoot lengths were 7.64±0.63 and 78±0.33 cm, respectively, when 0.1% (v/v) of the bio-extract was applied. This was most effective in increasing the vigor index of rice seedlings, with the highest value of 1466±66, which corresponded to an increase of 15.2% compared to the controls. However, increasing the concentration of the bio-extract (0.5-1.5%, v/v) drastically decreased the root and shoot elongation and vigor index of rice seedlings. These results indicate the bacterial diversity and quality of the bio-extract, and application should be done carefully at appropriate dilutions.